Distribuição e abundância da malacofauna epibentônica no Parracho de Maracajaú, RN, Brasil - Martinez, Aline Sbizera (2008)
The mollusks present a great taxon variety and life habits in coral reefs being good environmental indicators. It is important to know the distribution pattern of the mollusks and the processes that influence it, so that disturbances in sea ecosystems could be monitored. The present study aims to accomplish the inventory and distribution of epibenthic mollusks in the Parracho of Maracajaú. 23 sites in different habitats of the Parracho were settled: 11 in the reef habitat, 3 in the sandy bottom and 9 in the seagrass bed. Qualitative and quantitative samplings have been done through snorkeling and scuba diving. Three band transects (10m²) were sampled in each site and the data were obtained to each m² of the transect, where the species were counted and the environmental variables (rugosity and recovery of the substratum) were valued. The data were submitted to multivariate analyses in order to find possible distribution patterns that could be associated to the substratum variables. The diversity indexes were calculated for each reef sites and compared with each other. A number of 46 species were registered. The reef habit at should to be the richnest area while the sandy bottom was poorest one. In the reef habitat, the mollusks were associated to rugosity and recovering of frondose algae and zoanthids, while for the seagrass bed, the animals exhibited a richness variation associated to the muddy and sandy sediment. There were found 3 species economically explored, what requires an appropriate management for the maintenance and conservation of the area resources in a sustainable way